1974
DOI: 10.1677/joe.0.0600473
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Corticosterone Levels During Pregnancy in the Mouse: The Relative Contributions of the Adrenal Glands and Foeto-Placental Units

Abstract: SUMMARY Plasma corticosterone levels were measured throughout pregnancy and on the first day post partum in the mouse. During the first half of pregnancy plasma corticosterone levels rose from the non-pregnant value of 2·3 μg/100ml to 15·2 μg/100 ml on day 10. During the second half of pregnancy there was a sharp rise, levels reaching a peak of 138·3 μg/100ml on day 16. Following parturition there was a rapid fall to 18·3 μg/100 ml on the morning of the first day post partum. Adrenalectomy on day 15 resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(44 citation statements)
references
References 0 publications
5
39
0
Order By: Relevance
“…In dexamethasone-induced cells and in neonatal liver, the abundance of Amy-J-L transcripts increased approximately 15-fold. Concomitant with the increase in liver amylase just before birth, there is an increase in circulating glucocorticoid levels (2,9,41). This suggests that the Amy-i liver promoter is regulated by glucocorticoids during development in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In dexamethasone-induced cells and in neonatal liver, the abundance of Amy-J-L transcripts increased approximately 15-fold. Concomitant with the increase in liver amylase just before birth, there is an increase in circulating glucocorticoid levels (2,9,41). This suggests that the Amy-i liver promoter is regulated by glucocorticoids during development in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…For the first time, we have shown that throughout pregnancy, the circadian profiles of 11-DHC generally paralleled the corresponding corticosterone profiles, including the apparent loss of rhythmicity on day 18. The ratio of corticosterone:11-DHC increased substantially on day 14, possibly due to greater plasma CBG binding of corticosterone and an associated reduction in the proportion metabolized to 11-DHC (Barlow et al 1974(Barlow et al , 1975. This conversion is catalyzed by the 11b-hydroxysteroid dehydrogenase enzymes (11b-HSD1 and 11b-HSD2), and opposite changes in their expression occur in the two placental zones late in rodent pregnancy (Mark et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone may exert its effect on the functional differentiation of T cells partly through GR. During the second half of pregnancy in mice, plasma corticosterone levels reach a peak of 4 M on day 16, ϳ60 times the nonpregnant resting level (45). Most of the plasma corticosterone is of adrenal origin, and the remaining portion of the corticosterone is feto-placental in origin (45).…”
Section: Discussionmentioning
confidence: 99%